Nyanyian Jemaat Sebagai Upaya Menghadirkan Eklesiologi Yang Komunikatif - Novenrik Tambunan (Institut Agama Kristen Negeri Tarutung, 2022)
Abstract:The starting point of this paper is about how the congregation can understand and apply the ecclesiology of their church which has always been struggled, compiled and understood by those with a theological education background or those who have ordained positions in the church. Church members (lay) rarely touch this matter even though both ordinary church members and church officials are called together in the fellowship of believers to witness God's work for the world. This paper offers congregational singing as a way for the church to listen and accommodate the congregation's opinion on ecclesiology in their own way. Thus, the church is expected to instill a communicative understanding of ecclesiology act.Abstrak:Titik berangkat tulisan ini adalah tentang bagaimana jemaat dapat memahami dan mengaplikasikan eklesiologi gerejanya yang selama ini selalu digumuli, disusun dan dipahami oleh mereka yang berlatar-belakang pendidikan teologi atau mereka yang memiliki jabatan tahbisan di gereja. Anggota jemaat (awam) jarang sekali menyentuh hal ini padahal baik anggota jemaat biasa maupun para pejabat gereja dipanggil bersama dalam persekutuan orang percaya untuk mempersaksikan karya Allah bagi dunia. Tulisan ini menawarkan nyanyian jemaat sebagai cara gereja dalam menyimak dan mengakomodir pendapat jemaat mengenai eklesiologi dengan cara mereka. Dengan demikian, gereja diharapkan dapat menanamkan pemahaman eklesiologi yang komunikatif.